The extent to which physical education teachers make decisions in certain school situations, from the perspective of physical education teachers in the primary stage. - kaid aazen, aabdo (sports creativity, 2025)
Despite the differences in school situations, we find that male and female physical education teachers are among those most concerned with dealing with such situations. This is not only for male teachers but for female teachers, as both are concerned with such situations. However, there are some situations that may be more expected of male physical education teachers than female teachers due to the nature of Arab society in general and Yemeni society in particular. It appears from these situations that the school administration throws many of these situations onto the physical education teachers, perhaps due to their distinguished field activity, and also due to the breadth of their relationships with the administration, teachers and students within the school, as well as their relationships and activities outside the school. Thus, they are more experienced and adept than other teachers in quickly finding solutions to school problems and situations.